Drug-induced nephrotoxicity - Dhodi, Dinesh K.; Bhagat, Sagar B.; Pathak, Deepanjali; Patel, Sadiq B. (International Journal of Basic & Clinical Pharmacology, 2017)
Drug-induced nephrotoxicity is an extremely common condition and is responsible for a variety of pathological effects on the kidneys. Drug-induced acute renal failure (ARF) accounted for 20% of all ARF cases. Drugs showed to cause nephrotoxicity exert their toxic effects by one or more common pathogenic mechanisms. Although it is impossible to present all the drugs causing the nephrotoxicity, this article will summarize the mechanism of injury associated with particular common medications, discuss clinical presentations, renal markers, and evaluate strategies that prevent or minimize renal injury. Drug-induced nephrotoxicity tends to be more common among certain patients and in specific clinical situations. Therefore, successful prevention requires knowledge of pathogenic mechanisms of renal injury, patient-related risk factors, drug-related risk factors, and preemptive measures, coupled with vigilance and early intervention. General preventive measures include using alternative non-nephrotoxic drugs whenever possible; correcting risk factors, if possible; assessing baseline renal function before initiation of therapy, followed by adjusting the dosage; monitoring renal function and vital signs during therapy, and avoiding nephrotoxic drug combinations. Surprisingly, little information is available to guide us with respect to avoiding complications in critical illness; therefore, it is necessary to follow the guidelines.